2021
DOI: 10.1093/biolre/ioab215
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 induces gene and protein expression related to maternal-conceptus immune tolerance in bovine endometrium

Abstract: Conceptus secretory factors include galectins, a family of carbohydrate binding proteins that elicit cell adhesion and immune suppression by interacting with intracellular and extracellular glycans. In rodents, galectin-1 (LGALS1) promotes maternal-fetal immune tolerance in the decidua through expansion of tolerogenic CD11c+ dendritic cells, increased anti-inflammatory IL-10, and activation of FOXP3+ regulatory T cells (Treg). This study characterized galectin expression in early ruminant conceptuses and endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Wilsher and others proposed a protective role of LGALS1 expressed in the equine trophoblast from the maternal immune system 93 . This is also supported by a recent study in cattle where conceptus LGALS1 has been suggested to confer maternal‐conceptus immune tolerance 94 …”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Wilsher and others proposed a protective role of LGALS1 expressed in the equine trophoblast from the maternal immune system 93 . This is also supported by a recent study in cattle where conceptus LGALS1 has been suggested to confer maternal‐conceptus immune tolerance 94 …”
Section: Discussionmentioning
confidence: 62%
“… 93 This is also supported by a recent study in cattle where conceptus LGALS1 has been suggested to confer maternal‐conceptus immune tolerance. 94 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce this possibility, we have accurately characterized EVs according to current ISEV guidance (26). Moreover, previous work has sown that conceptus-derived proteins do have a functional effect on the endometrium (4, 11, 27), demonstrating that there are functional roles for these proteins identified in conceptus-conditioned medium (CCM). The differences observed are therefore due to differences in composition of the EVs themselves as no changes in size, concentration, or indeed markers were observed in EVs from different source conceptuses.…”
Section: Discussionmentioning
confidence: 99%
“…While studying maternal-conceptus immune tolerance in bovine endometrium Chaney et al assayed a set of eight potential reference genes in terms of their expression stability 22 . For caruncular tissues treated with either progesterone (P4), recombinant bovine galectin-1 (rbLGALS1) or their combination, ring finger protein 11 gene ( RNF11 ) and H3 histone family member 3A gene ( H3F3A ) were chosen as internal controls.…”
Section: Discussionmentioning
confidence: 99%